Description of Lactobacillus backi sp. nov., an Obligate Beer-Spoiling Bacterium - Bohak, Ingrid; Thelen, Karin; Beimfohr, Claudia (BrewingScience, 2006)
Lactic acid bacteria that are able to spoil beer comprise a limited number of bacteria of the genera Lactobacillus and Pediococcus. Five Gram-positive isolates of uncertain taxonomic position causing turbidity, sediments and decreasing pH-value were isolated from lager, pils and wheat beers from different breweries in Germany and Italy. Physiological and biochemical studies of these strains showed a homogeneous group of organisms. The 16S rDNA sequence analysis of three of the five isolates revealed that they formed a phylogenetically distinct line within the genus Lactobacillus and have clearly less than 97% 16S rDNA sequence similarities to any other species. All strains were homofermentative, producing D(L)-lactic acid. Based on the data presented in this study the new species Lactobacillus backi is proposed. The type strain of L. backi is DSM 18080T (LMG 23555T).